Determinación del índice de prevalencia de brucelosis bovina en el cantón Naranjal provincia del Guayas - Barros Morales, Carlos Ivan (2015)
Bovine Brucellosis is a contagious bacterial disease that causes serious damage in livestock breeding and production chain, while as transmissible to humans, zoonotic disease has a direct impact on quality of life and public health. This research was conducted: to determine the prevalence rate of bovine brucellosis in the Canton Naranjal, 500 blood samples obtained on cattle farms of small and medium milk producers were examined. The method used was the diagnostic test Rose Bengal (Card Test) which allows expression of rapid and reliable results. Blood samples were taken from the coccygeal vein with a needle attached to a 5 mL vacutainer tube 0% of the samples, randomly selected from different ranches, were taken to the Microbiology Laboratory of The Agricultural Sciences Academic for a confirmatory test. The results showed a prevalence rate of 0% for Brucella abortus which shows a very favorable outcome in cattle farms of Canton Naranjal.